Defining the fracture population in a pragmatic multicentre randomised controlled trial: PROFHER and the Neer classification of proximal humeral fractures. Issue 10 (October 2016) - Handoll, H. H. G.; Brealey, S. D.; Jefferson, L.; Keding, A.; Brooksbank, A. J.; Johnstone, A. J.; Candal-Couto, J. J.; Rangan, A.
Abstract : Objectives: Accurate characterisation of fractures is essential in fracture management trials. However, this is often hampered by poor inter-observer agreement. This article describes the practicalities of defining the fracture population, based on the Neer classification, within a pragmatic multicentre randomised controlled trial in which surgical treatment was compared with non-surgical treatment in adults with displaced fractures of the proximal humerus involving the surgical neck. Methods: The trial manual illustrated the Neer classification of proximal humeral fractures. However, in addition to surgical neck displacement, surgeons assessing patient eligibility reported on whether either or both of the tuberosities were involved. Anonymised electronic versions of baseline radiographs were sought for all 250 trial participants. A protocol, data collection tool and training presentation were developed and tested in a pilot study. These were then used in a formal assessment and classification of the trial fractures by two independent senior orthopaedic shoulder trauma surgeons. Results: Two or more baseline radiographic views were obtained for each participant. The independent raters confirmed that all fractures would have been considered for surgery in contemporaneous practice. A full description of the fracture population based on the Neer classification was obtained. The agreement between the categorisation at baseline (tuberosity involvement) and Neer classification as assessed by the two raters was only fair (kappa 0.29). However, this disparity did not appear to affect trial findings, specifically in terms of influencing the effect of treatment on the primary outcome of the trial. Conclusions: A key reporting requirement, namely the description of the fracture population, was achieved within the context of a pragmatic multicentre randomised clinical trial. This article provides important guidance for researchers designing similar trials on fracture management. Cite this article: H. H. G. Handoll, S. D. Brealey, L. Jefferson, A. Keding, A. J. Brooksbank, A. J. Johnstone, J. J. Candal-Couto, A. Rangan. Defining the fracture population in a pragmatic multicentre randomised controlled trial: PROFHER and the Neer classification of proximal humeral fractures. Bone Joint Res 2016;5:481–489. DOI: 10.1302/2046-3758.510.BJR-2016-0132.R1.